2012
DOI: 10.1007/s12263-012-0287-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymorphisms in nucleotide-binding oligomerization domains 1 and 2 on biomarkers of the metabolic syndrome and type II diabetes

Abstract: The innate immune receptor toll-like receptor 4 (TLR4) has been implicated in mediating some of the effects of dietary lipids on inflammation and type 2 diabetes (T2D). Similar to TLR4, the nucleotide-binding oligomerization domains (Nods) 1 and 2 are also proteins of innate immunity, which can respond to lipids and initiate pro-inflammatory signalling that plays a role in the aetiology of T2D. The objective was to determine the effect of Nod1 (Glu266Lys) and Nod2 (Ser268Pro) genotypes on factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
3
15
0
1
Order By: Relevance
“…Supporting these findings, other studies have described that NOD1 activation promotes insulin resistance in adipocytes and hepatocytes [7,24,27,28]. Supporting these findings, other studies have described that NOD1 activation promotes insulin resistance in adipocytes and hepatocytes [7,24,27,28].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Supporting these findings, other studies have described that NOD1 activation promotes insulin resistance in adipocytes and hepatocytes [7,24,27,28]. Supporting these findings, other studies have described that NOD1 activation promotes insulin resistance in adipocytes and hepatocytes [7,24,27,28].…”
Section: Discussionsupporting
confidence: 59%
“…As previous evidence suggests that NOD1 can participate in diabetes [7,[27][28][29], we have evaluated the expression of NOD1 in the myocardium of a transgenic db mouse model. db mice manifest several indicators common to patients with Type 2 diabetes, including obesity, hyperglycaemia, hyperinsulinaemia and depressed cardiac function [30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to invading pathogens, both NOD1 and NOD2 are also similarly activated by fatty acids and induce non‐infectious chronic inflammation, which is referred to as sterile inflammation. NOD1 may act as an intracellular lipid sensor affecting insulin sensitivity . Bremer et al previously demonstrated significantly increased levels of circulating markers of inflammation in nascent MetS subjects compared to controls, even after adjustment for adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…Further supporting a role for NOD genes in dietary fat‐induced inflammatory responses and insulin resistance, a recent study has linked the Glu266Lys polymorphism in the NOD1 gene between dietary saturated fatty acid intake and insulin sensitivity, despite a lack of correlation with other classical biomarkers of the metabolic syndrome (including waist circumference, triglycerides, high density lipoproteins, glucose, systolic and diastolic blood pressure; Cuda et al ., ). In summary, recent evidence illustrate the complex relationship between systems of immune defence and metabolic regulation but may also offer exciting new therapeutic avenues in type 2 diabetes.…”
Section: Nod1 and Metabolic Diseasesmentioning
confidence: 97%